Purification and characterization of a novel GH1 beta-glucosidase from Jeotgalibacillus malaysiensis - Liew, Kok Jun; Lim, Lily; Woo, Hui Ying; Chan, Kok Gan; Shamsir, Mohd Shahir; Goh, Kian Mau (Elsevier, 2018)
Beta-glucosidase (BGL) is an important industrial enzyme for food, waste and biofuel processing. Jeotgalibacillus is an understudied halophilic genus, and no beta-glucosidase from this genus has been reported. A novel beta-glucosidase gene (1344 bp) from J. malaysiensis DSM 28777T was cloned and expressed in E. coli. The recombinant protein, referred to as BglD5, consists of a total 447 amino acids. BglD5 purified using a Ni-NTA column has an apparent molecular mass of 52 kDa. It achieved the highest activity at pH 7 and 65 °C. The activity and stability were increased when CaCl2 was supplemented to the enzyme. The enzyme efficiently hydrolyzed salicin and (1 → 4)-beta-glycosidic linkages such as in cellobiose, cellotriose, cellotetraose, cellopentose, and cellohexanose. Similar to many BGLs, BglD5 was not active towards polysaccharides such as Avicel, carboxymethyl cellulose, Sigmacell cellulose 101, alpha-cellulose and xylan. When BglD5 blended with Cellic® Ctec2, the total sugars saccharified from oil palm empty fruit bunches (OPEFB) was enhanced by 4.5%. Based on sequence signatures and tree analyses, BglD5 belongs to the Glycoside Hydrolase family 1. This enzyme is a novel beta-glucosidase attributable to its relatively low sequence similarity with currently known beta-glucosidases, where the closest characterized enzyme is the DT-Bgl from Anoxybacillus sp. DT3-1.